Management Graduates: A Tracer Study from Universitas XXX - Risza Putri Elburdah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tracer Study is research that can provide useful information for evaluating the results of higher education and can then be used to improve and guarantee the quality of higher education. This research uses a quantitative research approach with a survey research type. The research population is Management Department graduates who graduated in 2019 and 2020. The sample used is saturated sampling, where the entire population is sample members. The research results were analyzed using descriptive statistics and information about graduates was extracted including the number of graduates. Includes who the graduates are, employment status of graduates, waiting time for graduates, coverage of graduates' workplaces. The research results show that Management graduates are able to survive as private sector employees. Horizontal Alignment reaches 90%, which means that most management study program graduates have worked in fields relevant to their study background.